Frontispiz: Synthesis and Two‐Dimensional Chiral Surface Self‐Assembly of a π‐Conjugated System with Three‐Fold Symmetry: Benzotri(7‐Azaindole). (18th January 2021) - Rodríguez, Luis M.; Gómez, Paula; Más‐Montoya, Miriam; Abad, José; Tárraga, Alberto; Cerdá, Jorge I.; Méndez, Javier; Curiel, David
Abstract : Selbstorganisation Das rationale Design, die Synthese und die zweidimensionale Selbstorganisation von Benzotri(7‐azaindol) werden im Forschungsartikel von Javier Méndez, David Curiel et al. auf S. 1810 vorgestellt.